ANALISIS PENGEMBANGAN BUMDES DI KECAMATAN KAMPA KABUPATEN KAMPAR - Yona Afrina (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The main objective of this research is to analyze the development of Bumdes in Kampa District, Kampar Regency. The research was conducted in Kampar District, Riau Province, which is one of the 12 districts / cities in Riau Province. The data used in this study are primary and secondary data. Primary data (first-hand data) is data obtained directly from research subjects while secondary data is supporting data that has been published and obtained from books, magazines, and so on related to this research. In this research, Analyze Development of Bumdes, this type of field research analyzes the data using descriptive qualitative methods. Based on the results of the study, it is known that in the development analysis of the 5 bumdes studied, the researcher only compared 2 Bumdes based on the profitability ratio. From the results of this study, the profitability ratio at Bumdes Sejahtera, namely Return On Asset, decreases every year but is still in the very good criteria stage, then Return On Equuity at a prosperous bumdes fluctuates but is still in very good criteria, Operational Expenses to Operating Income increase each year, therefore the criteria are very good while for Net profit Margin decreases every year so it has very bad criteria this is due to the large number of bad loans from borrowers. Bumdes In Kampa District, there are almost the same obstacles, in general, such as Human Resource Weaknesses, inaccurate selection of business units and business management. From the results of this study, it is hoped that BUMDes in Kampa District, Kampar Regency, will further enhance the development of the village's original local potential. That way, the economy in each village will continue to increase and be independent.